Effects of Patient and Family-Centered Care on Quality of Care in Pediatric Patients: A Systematic Review - Tuti Seniwati; Dessie Wanda; Nani Nurhaeni (Nurse Media Journal of Nursing, 2023)
Background: Patient and family-centered care is one approach that is applied in pediatric care in various hospital settings to improve the quality of care. However, information related to the results of the entire study and its intervention model has not been identified effectively in child health care.Purpose: This study aimed to describe and assess the effects of patient and family-centered care on the quality of care in pediatric patients.Methods: A systematic review was used as a method in this study. Seven databases were used, including ScienceDirect, Scopus, ProQuest, EBSCO, Sage Journal, Tailor and Francis, and PubMed to search the literature for relevant published reviews that determined patient and family-centered care interventions between 2011 and 2021. The synthesis without meta-analysis guidelines was used to analyze the data in this review. The data were further analyzed by critically assessing the quality of the articles using the JBI and CASP checklists.Results: From a total of 29.780 articles identified, fifteen articles were included in this review. Several models of patient and family-centered care interventions were identified, such as family-centered care, family-centered communication program, family-integrated care, family nurture intervention, family empowerment, parent participation, close collaboration, mother-nurse partnership program, and the newborn individualized developmental care and assessment program. From those models, the outcomes for quality of care were related to the pediatric quality of life, length of stay, patient safety, parent satisfaction, parent psychological response, and parent involvement and partnership with staff.Conclusion: The shreds of evidence indicate that patient and family-centered care can improve the quality of care in the pediatric patients. It is recommended that patient and family-centered care can be implemented in pediatric care by increasing the participation of family during treatment.